Fundamentals of English Grammar,Third Edition Teacher’s Guide - Azar, Betty Schrampfer (Longman, 2014)
The principal aims of Fundamentals of English Grammar are to present clear, cogent information about English grammar and usage, to provide extensive and varied practice that encourages growth in all areas of language use, and to be interesting, useful, and fun for student and teacher alike. The approach is eclectic, seeking to balance form-focused language-learning activities with abundant opportunities for engaged and purposeful communicative interaction. Most students find it helpful to have special time set aside in their English curriculum to focus on grammar. Students generally have many questions about English grammar and appreciate the opportunity to work with a text and teacher to make some sense out of the bewildering array of forms and usages in this strange language. This understanding provides the basis for advances in usage ability in a relaxed, accepting classroom that encourages risk-taking as the students experiment, both in speaking and writing, with ways to communicate their ideas in a new language. Teaching grammar does not mean lecturing on grammatical patterns and terminology. It does not mean bestowing knowledge and being an arbiter of correctness. Teaching grammar is the art of helping students make sense, little by little, of a huge, puzzling construct, and engaging them in various activities that enhance usage abilities in all skill areas and promote easy, confident communication. The text depends upon a partnership with a teacher; it is the teacher who animates and directs the students’ language-learning experiences. In practical terms, the aim of the text is to support you, the teacher, by providing a wealth and variety of material for you to adapt to your individual teaching situation. Using grammar as a base to promote overall English usage ability, teacher and text can engage the students in interesting discourse, challenge their minds and skills, and intrigue them with the power of language as well as the need for accuracy to create understanding among people.